Enabling Electron Injection for Microbial Electrosynthesis with n‐Type Conjugated Polyelectrolytes (Adv. Mater. 37/2022). Issue 37 (15th September 2022) - Quek, Glenn; Vázquez, Ricardo Javier; McCuskey, Samantha R.; Kundukad, Binu; Bazan, Guillermo C.
Abstract : Microbial Electrosynthesis Microbial electrosynthesis holds the promise of sustainable chemical production. In article number 2203480, Guillermo C. Bazan and co‐workers show that 3D living biocomposites integrating electroactive bacteria with an n‐type conjugated polyelectrolyte allow efficient long‐range electron transfer from electrode to living cells, thereby enabling microbial electrosynthesis. The one‐step self‐assembly process offers a simple and effective strategy to improve bioelectrochemical systems.